1985
DOI: 10.1143/jjap.24.279
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Diffusion Coefficient of Oxygen in Silicon

Abstract: The solubility and diffusion coefficient of oxygen in silicon between 1000°C and 1375°C were examined by charged particle activation analysis with the 16O(3He, p)18F reaction, in which oxygen was activated with an equal probability over the depth of up to 250 µm by a specially devised apparatus. Silicon wafers of known histories were heated in oxygen or argon for 12 to 473 hours, and the resultant oxygen depth profiles were determined by the activation, subsequent stepwise etching and 18F activity measurement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…The following techniques are considered as direct measurements of oxygen concentration in Si: secondary ion mass spectrometry (SIMS)(3-7), charged particle activation (CPA) (8,9), and infrared absorption (IR). (10)(11)(12)(13) The first two techniques have the sensitivity to determine depth profiles, from which both diffusivities and solubilities can be obtained; impurity distributions from in-diffusions are described by C(x,t) = Co erfc (x/2lt) and out-diffusions of supersaturated CZ Si by C(x,t) = Co + (C, -Co) erf (x/2VDt), where Co is the equilibrium solubility (observed at the surface of the Si crystal) and D and t are diffusivity and time, respectively.…”
Section: Direct Methods Of Measuring 0 In Simentioning
confidence: 99%
“…The following techniques are considered as direct measurements of oxygen concentration in Si: secondary ion mass spectrometry (SIMS)(3-7), charged particle activation (CPA) (8,9), and infrared absorption (IR). (10)(11)(12)(13) The first two techniques have the sensitivity to determine depth profiles, from which both diffusivities and solubilities can be obtained; impurity distributions from in-diffusions are described by C(x,t) = Co erfc (x/2lt) and out-diffusions of supersaturated CZ Si by C(x,t) = Co + (C, -Co) erf (x/2VDt), where Co is the equilibrium solubility (observed at the surface of the Si crystal) and D and t are diffusivity and time, respectively.…”
Section: Direct Methods Of Measuring 0 In Simentioning
confidence: 99%
“…[29][30][31][32] From the above considerations, it can safely be concluded that h 4 is larger than 4.7 eV, the more reliable value being 5.9 or 6 eV.…”
Section: Formation Energy Of Oxygen Vacancies In Siomentioning
confidence: 99%
“…The uncertainties in the converted value of O i concentrations (Fig. 2) are possible to occur due to possible errors in the data treatment and the effect of wafer's surface on the peak height is high especially for the thin wafers (o500 mm thick) [18].…”
Section: Resultsmentioning
confidence: 99%